Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.4102/sajpsychiatry.v18i2.351
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective chart review of the clinical and psychosocial profile of psychotic adolescents with co-morbid substance use disorders presenting to acute adolescent psychiatric services at Tygerberg Hospital

Abstract: <p><strong>Background.</strong> A large number of adolescents meet criteria for ‘dual diagnosis’ (a psychiatric disorder plus co-morbid substance use disorder (SUD), which prolongs treatment response and complicates intervention strategies. The current service model in Cape Town divides the care of such patients into psychiatric treatment and a separate substance use intervention. Child and adolescent mental health services face the challenge of high rates of readmission of adolescents into p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 26 publications
4
17
1
Order By: Relevance
“…This study reported some important differences in the socio-demographic profile of EOP and other mentally ill adolescents, which we believe reflect disparities in access to mental health services for the latter group of adolescents. Although the profile of EOP adolescents closely mirrors the general population demographics and is consistent with the literature, 9,15 youth of Black ethnicity, rural residence and low socioeconomic status were under-represented in the control group of non-psychotic adolescents. Although risk factors related to socioeconomic status and ethnicities are associated with the development of psychosis, 16 and may in part account for some demographic characteristics of the EOP group, one has to consider alternative explanations.…”
Section: Disparities In Mental Health Care Accesssupporting
confidence: 82%
See 1 more Smart Citation
“…This study reported some important differences in the socio-demographic profile of EOP and other mentally ill adolescents, which we believe reflect disparities in access to mental health services for the latter group of adolescents. Although the profile of EOP adolescents closely mirrors the general population demographics and is consistent with the literature, 9,15 youth of Black ethnicity, rural residence and low socioeconomic status were under-represented in the control group of non-psychotic adolescents. Although risk factors related to socioeconomic status and ethnicities are associated with the development of psychosis, 16 and may in part account for some demographic characteristics of the EOP group, one has to consider alternative explanations.…”
Section: Disparities In Mental Health Care Accesssupporting
confidence: 82%
“…Lifetime prevalence rates of alcohol, nicotine and cannabis use in this study were high compared with an adolescent in-patient study in Israel, 1 but comparable with previous adult 19,20 and local adolescent studies. 9 Different definitions of substance use are likely to account for significant variability in substance use prevalence rates in the literature. 2 The prevalence of current cannabis use was higher in adolescents with EOP and more common in males as has been reported previously.…”
Section: Cannabis and Other Substance Usementioning
confidence: 99%
“…For example, in a study in Durban, South Africa, 61.8% of adolescents (aged 10-18 years) admitted with psychotic symptoms reported lifetime cannabis use; 9 while cannabis was the most common debut drug reported in adolescents with psychosis at Tygerberg Hospital in the Western Cape, South Africa. 10 In view of the high prevalence of comorbid cannabis use in adolescents presenting to mental health care services, we examine this association in greater detail. Whilst we recognise that mental illness may render adolescents more vulnerable to substance use, there is growing evidence that primary substance use is associated with increased risk for development of mental disorders; and furthermore that comorbid cannabis use impacts negatively on the clinical features and prognosis of these mental disorders.…”
Section: Scope Of Cannabis Use In South African Adolescentsmentioning
confidence: 99%
“…These effects seem to escalate when grouped together, as chaotic use patterns are more prominent (Rassool, 2011:36). Some of the effects associated with DD include the following: shorter periods of recovery; more visits to emergency units and hospitalisation; higher rates of suicidal thoughts and attempts; frequent displays of impulsivity and violence; higher occupational impairment and school drop-out rates; regular non-adherence to treatment; mixed mood states; higher levels of anxiety disorders; diminished quality of life; and poor treatment outcomes associated with HIV and TB (Lachman et al, 2012;Rassool, 2011:22).…”
Section: Dual Diagnosis: Causes Effects and Treatmentmentioning
confidence: 99%
“…Effective treatment outcomes greatly depend on early detection as, with time, symptoms become so intertwined that determining where one disorder ends and the other begins becomes impossible (Salloum, Pani & Cooke, 2010:354). Early detection is unfortunately not the norm, as individuals presenting with psychotic symptoms are generally not accepted into SUD treatment programmes in the RSA until symptoms have been treated (Lachman et al, 2012). Grobler (2012:6) acknowledges that as research on mental health care in the RSA is lacking, it is difficult to encourage people to seek treatment and provide accurate information.…”
Section: Dual Diagnosis: Causes Effects and Treatmentmentioning
confidence: 99%